Love the plot. A reflection on the processes of building connections in research and extension in community spaces for child and adolescent care (Cuadernos de Extensión Universitaria de la UNLPam, 2025)
In this paper we reflect on the way in which connections are built in research-extension experiences that engage us in dialogues with women workers in community care spaces serving children and adolescents from working-class areas in Córdoba. From the theoretical-practical contributions of critical extension, feminist perspective and “popular education”, we carry out this analysis of an extension experience that took place within the framework of a research initiative. Listening to the voices and knowledge of the protagonists of the community plot and paying close to the ways in which time is constructed in the interludes of extension provide nuances of interest for rethinking university activities methodologies and the forms of connections that are promoted.
Keywords: research-extension; relationships; care space; feminisms